2016
DOI: 10.1371/journal.pone.0164355
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of the Irrigation Solution Samples Collected during Vitrectomy for Idiopathic Epiretinal Membrane

Abstract: PurposeThe analysis of gene expression in idiopathic epiretinal membranes (iERMs) may help elucidate ERM formation and its pathology. Here, we conducted a case-control study, in order to determine the expression levels of cytokines and other genes in eyes with macular hole (MH) or iERM.MethodsTwenty eyes, obtained from seven male and 13 female patients, were included in the study. The average age of the study subjects was 69.1 ± 7.67 years, and 15 eyes had iERM, while five eyes had MH. Irrigation solution samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(49 reference statements)
1
9
0
Order By: Relevance
“…Gene expression analysis, performed through quantitative real time polymerase chain reaction, confirmed some findings previously described, including TGF-β2 and NGF upregulation [ 194 , 210 ]. In the VH of iERM Myojin and coworkers also assessed upregulation of IL-6, CXCL1 and the NF-κB subunit RELA [ 210 ], all related to aging and inflammation. However, the actual source of these molecules in eyes with iERMs is still unknown.…”
Section: Fibrogenic Biomarkers In the Vitreous Humor: Growth Factors ...supporting
confidence: 79%
See 1 more Smart Citation
“…Gene expression analysis, performed through quantitative real time polymerase chain reaction, confirmed some findings previously described, including TGF-β2 and NGF upregulation [ 194 , 210 ]. In the VH of iERM Myojin and coworkers also assessed upregulation of IL-6, CXCL1 and the NF-κB subunit RELA [ 210 ], all related to aging and inflammation. However, the actual source of these molecules in eyes with iERMs is still unknown.…”
Section: Fibrogenic Biomarkers In the Vitreous Humor: Growth Factors ...supporting
confidence: 79%
“…To this aim, they should be contextualized and corroborated by direct findings on the membranes. Indeed, the observation that the VEGF-A mRNA extracted from irrigation solution samples collected during vitrectomies from eyes with iERM is increased compared to samples from eyes with MHs [ 210 ] supports the notion that VEGF-A is produced within iERMs though it does not diffuse to the VH in detectable amounts.…”
Section: Fibrogenic Biomarkers In the Vitreous Humor: Growth Factors ...mentioning
confidence: 91%
“…[25] Histological studies have revealed that myofibroblasts, fibroblasts, clear cells, and macrophages may play roles in the occurrence and progression of iERM. [25] Myojin et al [26] examined the vitreous lavage fluid of participants with iERM (15 eyes) and found that pro-inflammatory genes were overexpressed (IL-6, GFAP, VEGFA, TGFB2, CXCL1, TNC, and RELA). Multiple interleukins (IL-1 IL-6, IL-13, IL-17) and TGF-β1, TGFβ2 interferon necrosis factor and other inflammatory factors are also involved in the formation of iERM.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple interleukins (IL-1 IL-6, IL-13, IL-17) and TGF-β1, TGFβ2 interferon necrosis factor and other inflammatory factors are also involved in the formation of iERM. [23,26] Furthermore, in the development of iERM, the RAS system is implicated. [23,27] RAS can induce retinal vascular inflammation and mediate and regulate the factors involved in iERM fibrosis (FGF2, GDNF, NGF, TGF-β1).…”
Section: Discussionmentioning
confidence: 99%
“…TGF β 2 expressions showed statistical differences between almost all study groups, except one (ERM group versus MH group). Myojin et al analysed gene expression in the irrigation solution collected during vitrectomy performed due to ERMs and MH and found that the expression levels of TGF β 2 and VEGF α were significantly higher in eyes with iERM versus MH [ 35 ]. Nonetheless, we found no differences in gene expression of VEGF α and TGF β 2 in ILM in patients suffering from ERM versus patients with MH.…”
Section: Discussionmentioning
confidence: 99%